ANCAMAN HIPOKSIA BAGI EKOSISTEM PESISIR; PENGGUNAAN INDEKS AMMONIA-ELPHIDIUM (A-E) SEBAGAI PROKSI - Ricky Rositasari (Pusat Penelitian Oseanografi LIPI, 2020)
Hypoxia is one of the aquatic phenomena caused by natural and/or anthropogenic factors. Eutrophication is the main trigger of hypoxia in coastal waters throughout the hemisphere. Hypoxia that occurs in aquatic ecosystems refers to the low concentration of dissolved oxygen in the water column to less than 2 mg/L. Hypoxia causes a double effect, low oxygen supply for biotic physiological process, and triggers ocean acidification. Prolonged hypoxic conditions will have a significant impact on the food webs in coastal waters and sea waters, further conditions will ultimately have an impact on capture-based fishing activities. The case of hypoxia in Indonesian coastal waters has not been widely revealed and has not been a concern to be understood or traced to its existence. Retrospective as well as actual traces of hypoxia were revealed, especially in the waters of Jakarta Bay. The retrospective study was carried out using proxies that have been used in various tropical and subtropical countries, the Ammonia-Elphidium (A-E) index (Foraminifera). The results show that several places in the coastal waters of Jakarta Bay and Semarang have experienced episodic hypoxic events for several centuries. A brief review of phenomenal hypoxic events in other parts of the world and preliminary information on recorded events in several Indonesian coastal waters are expected to open stakeholder awareness about further threats of hypoxia in Indonesian waters.